"Summary measure" statistic for assessing the outcome of treatment trials in relapsing-remitting multiple sclerosis - Liu, C. (BMJ Group, 1998)
OBJECTIVES—To review the outcome measures commonly used in phase III treatment trials of relapsing-remitting multiple sclerosis and to introduce a method of data analysis which is clinically appropriate for the often reversible disability in this type of multiple sclerosis. METHODS—The conventional end point measures for disability change are inadequate and potentially misleading. Those using the disability difference between study entry and completion do not take into account serial data or disease fluctuations. Rigid definitions of "disease progression" based on two measurements of change in disability several months apart, do not assess worsening after the defined "end point", nor the significant proportion of erroneous "treatment failures" which result from subsequent recovery from relapses that outlast the end point. Assessing attacks merely by counting their frequency ignores the variation in magnitude and duration. These problems can be largely circumvented by integrating the area under a disability-time curve (AUC), a technique which utilises all serial measurements at scheduled visits and during relapses to summarise the total neurological dysfunction experienced by an individual patient on any particular clinical scale during a study period. CONCLUSIONS—The "summary measure" statistic AUC incorporates both transient and progressive disability into an overall estimate of the dysfunction that was experienced by a patient during a period of time. It is statistically more powerful and clinically more meaningful than conventional methods of assessing disability changes, particularly for trials which are too short to expect to disclose major treatment effects on irreversible disability in patients with a fluctuating disease.